The role of motivation camp towards academic performance and time management among first year biomedical science students - Masre, Siti Fathiah; Ishak, Ismarulyusda; Mat Ludin, Arimi Fitri; Shamhari, Asma Afifah; Syed Idros, Syed 'Imran; Abdul Rahman, Nur Adilah; Baso, Shahira; Sim Nyam Joo, Funnyla; Jamaludin, Izzati; Omar, Nur Emynatasha; Jufri, Nurul Farhana (Life Sciences, Medicine and Biomedicine, 2020)
Background: Time management is one of the factors that may influence students’ academic performance in university. A cross-sectional study was carried out to evaluate the role of motivation camp programme towards time management among first-year undergraduate students of the Biomedical Science Programme, Universiti Kebangsaan Malaysia (UKM) by using a questionnaire.  Methods: A total of 32 students was categorized into group 1 and group 2 (n=16 per group), with group 1 is students who did not attend the motivational camp and group2 participated in the camp. Their academic performance in terms of Grade Point Average (GPA) was evaluated in semester 1 and 2 of the 2017/2018 session. A correlation test between total study hours and GPA in both semesters showed a weak correlation for group1 and group2. Independent T-test was also carried out to compare time management and GPA. Results: There is no significant difference between group1 and group2 in time planning; however, there is a significant difference (p